AVALIAÇÃO DOS MÉTODOS DE INSPEÇÃO PARA ATENDIMENTO ÀS NORMAS DO SISTEMA DE GESTÃO PREDIAL DA ABNT - Cardinal, Scheyla Maria; Pilz, Sílvio Edmundo; Costella, Marcelo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In order to use the inspection as a tool in a maintenance management system, the objective of this work was to find methods of inspecting buildings according to the Brazilian standards by analyzing their requirements. The 13 most relevant references that had a more detailed description of the inspection methods were selected, including two inspection standards, one from IBAPE (2012) and one from ASTM (2012). As a result, an overview of the types and objectives of the inspections was obtained. Although only the methods of Neto (2007) and Oliveira (2013) partially addressed the items under analysis, all methods studied contributed to gathering technical aspects necessary to propose a model of building maintenance management that is being developed together to the maintenance sector of an educational institution along with a master´s thesis. The main contributions are the help in the understanding of issues such as the necessary professional qualification depending on the objective of the inspection and technical aspects that should be taken into account in the execution of the activities.